(Epi)genetic variants of the sarcomere-desmosome are associated with premature utero-contraction in spontaneous preterm labor. (March 2021) - Wang, Jie; Luo, Xiucui; Pan, Jing; Dong, Xiaoyan; Tian, Xiujuan; Tu, Zhihua; Ju, Weina; Zhang, Meijiao; Zhong, Mei; De Chen, Charles; Flory, Michael; Wang, Yong; et al.
Highlights: Multiomics were applied to study premature utero-contraction in sPTB. Genomic variants in the sarcomere gene TTN were identified in sPTB. Epigenetic regulation of long non-coding RNAs were identified in gene TPM3 . Methylomic profiles were identified in sarcomeric genes/loci. Differential expression of transcripts associates with premature utero-contraction. Abstract: Spontaneous preterm birth is a syndrome with clinical and genetic heterogeneity. Few studies have focused on the genetic and epigenetic defects and pathogenic mechanisms associated with premature uterine contraction in spontaneous preterm birth. The objective of this study was to investigate the (epi)genetic variations associated with premature uterine contraction of spontaneous preterm birth. A systems biology approach with an integrated multiomic study was employed. Biobanked pregnancy tissues selected from a pregnancy cohort were subjected to genomic, transcriptomic, methylomic, and proteomic studies, with a focus on genetic loci/genes related to uterine muscle contraction, specifically, genes associated with sarcomeres and desmosomes. Thirteen single nucleotide variations and pathogenic variants were identified in the sarcomere gene, TTN, which encodes the protein Titin, from 146 women with spontaneous preterm labor. Differential expression profiles of five long non-coding RNAs were identified from loci that overlap with four sarcomeric genes. Longitudinally, the long non-coding RNA of gene TPM3 that encodes the protein tropomysin 3 was found to significantly regulate the mRNA of TPM3 in the placenta, compared to maternal blood. The majority of genome methylation profiles related to premature uterine contraction were also identified in the CpG promoters of sarcomeric genes/loci. Differential expression profiles of mRNAs associated with premature uterine contraction showed 22 genes associated with sarcomeres and three with desmosomes. The results demonstrated that premature uterine contraction was associated mainly with pathogenic variants of the TTN gene and with transcriptomic variations of sarcomeric premature uterine contraction genes. This association is likely regulated by epigenetic factors, including methylation and long non-coding RNAs.